Investigation on the Controllable Synthesis of Colorized and Magnetic Polystyrene Beads With Millimeter Size via In Situ Suspension Polymerization - Yan, Juntao; Wu, Hua; Huang, Pan; Wang, Yourong; Shu, Bowang; Li, Xiaofang; Ding, Deng; Sun, Ya; Wang, Chunlei; Wu, Jian; Sun, Linbing (Frontiers in Chemistry, 2022)
A series of colorized and magnetic polystyrene/Fe3O4 (PS/Fe3O4) composite beads with millimeter size are successfully synthesized by introducing hydrophobic Fe3O4 via in-situ suspension polymerization of styrene for the first time. Effects of hydrophobic Fe3O4 content, stirring speed and surfactant dosage on the macromorphology and particle size of PS/Fe3O4 beads are systematically investigated to realize the controllable synthesis. Moreover, three kinds of hydrophobic pigments are also employed to synthesize colorized polystyrene, which demonstrates the versatility, simplicity and wide applicability of the proposed method. Scanning electron microscopy (SEM) and element mapping (EM) images demonstrated that the hydrophobic Fe3O4 are well dispersed in the polystyrene matrix. Thermogravimetric analysis (TGA) exhibits that the resultant PS/Fe3O4 beads possess a better thermal stability than that of neat PS. PS/Fe3O4 beads have a promising application in the fields of colorized extruded PS board, colorized expanded PS foam particle and board.